2010
DOI: 10.1111/j.1744-7348.2010.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gossypium species for resistance to cotton leaf curl Burewala virus

Abstract: Cotton leaf curl disease (CLCuD), caused by cotton leaf curl Burewala virus (CLCuBV), has emerged as a major threat to cotton production in Pakistan. Resistance to CLCuBV was evaluated in cultivated and wild cotton genotypes representing six Gossypium species by visual symptom scoring and virus assessment using PCR tests. Considerable variation in responses was observed when using whitefly and graft transmission to inoculate Gossypium genotypes with CLCuBV in field and greenhouse experiments. Under field evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 26 publications
4
73
0
Order By: Relevance
“…For grafting studies, ten pots each for each variety were sown in glass house. Graft inoculation of the plants with CLCuV-B was done by following the bottle shoot grafting method (Akhtar et al, 2002(Akhtar et al, , 2010. Results showed that number of days taken to appear the symptoms (after grafting) in case of NIAB-2008 were 14-20 compared to 12-18 of MNH-786 (Table 7).…”
Section: Pathological Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For grafting studies, ten pots each for each variety were sown in glass house. Graft inoculation of the plants with CLCuV-B was done by following the bottle shoot grafting method (Akhtar et al, 2002(Akhtar et al, , 2010. Results showed that number of days taken to appear the symptoms (after grafting) in case of NIAB-2008 were 14-20 compared to 12-18 of MNH-786 (Table 7).…”
Section: Pathological Studiesmentioning
confidence: 99%
“…For grafting studies, ten pots for each variety were sown in glass house. Plants were graft inoculated with CLCuV-B following the methodology of bottle shoot grafting method ( Akhtar et al, 2002Akhtar et al, , 2010. Entomological studies regarding its response to sucking pests and damage by bollworms were conducted under optimized spray conditions at NIAB Faisalabad.…”
Section: Screening For Cotton Leaf Curl Virus Disease and Insect Pestsmentioning
confidence: 99%
“…arboreum (also known as Asiatic cotton) germplasm collection is an important genetic resource for tetraploid cotton improvement. G. arboreum has certain inherent qualities, which the tetraploids lack, like the ability to withstand drought and salinity (Maqbool et al 2010;Tahir et al 2011) and remarkable tolerance to several pests and disease, including bollworms (Dhawan et al 1991), aphids and leafhoppers (Nibouche et al 2008), rust, fungal (Wheeler et al 1999) and viral (Mehetre et al 2004;Akhtar et al 2010) diseases. Natural G. arboreum fibers display various colours (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It has inherent resistance to various biotic (Akhtar et al 2010) and abiotic stresses (Tahir et al 2011); tetraploids lack these qualities (Kulkarni 2002). Natural G. arboreum fibres display various colours (e.g.…”
mentioning
confidence: 99%